Towards standardization of measuring anxiety and depression: Differential item functioning for language and Dutch reference values of PROMIS item banks. - Ellen B M Elsman; Gerard Flens; Edwin de Beurs; Leo D Roorda; Caroline B Terwee (PLoS ONE, 2022)
Introduction The outcomes anxiety and depression are measured frequently by healthcare providers to assess the impact of a disease, but with numerous instruments. PROMIS item banks provide an opportunity for standardized measurement. Cross-cultural validity of measures and the availability of reference values are prerequisites for standardized measurement. Methods PROMIS Anxiety and Depression item banks were completed by 1002 representative Dutch persons. To evaluate cross-cultural validity, data from US participants in PROMIS wave 1 were used and differential item functioning (DIF) was investigated, using an iterative hybrid of logistic regression and item response theory. McFadden's pseudo R2-change of 2% was the critical threshold. The impact of any DIF on full item banks and short forms was investigated. To obtain Dutch reference values, T-scores for anxiety and depression were calculated for the complete Dutch sample, and age-group and gender subpopulations. Thresholds corresponding to normal limits, mild, moderate and severe symptoms were computed. Results In both item banks, two items had DIF but with minimal impact on population level T-scores for full item banks and short forms. The Dutch general population had a T-score of 49.9 for anxiety and 49.6 for depression, similar to the T-scores of 50.0 of the US general population. T-scores for age-group and gender subpopulations were also similar to T-scores of the US general population. Thresholds for mild, moderate and severe anxiety and depression were set to 55, 60 and 70, identical to US thresholds. Conclusions The limited number of items with DIF and its minimal impact, enables the use of standard (US) item parameters and comparisons of scores between Dutch and US populations. The Dutch reference values provide an important tool for healthcare professionals and researchers to evaluate and interpret symptoms of anxiety and depression, stimulating the uptake of PROMIS measures, and contributing to standardized outcome measurement.